Polyester film

JP2025023457APending Publication Date: 2025-02-17TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023127581
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、工程安定性を確保しつつも着色が少ないポリエステルフィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023457000001
    Figure 2025023457000001
  • Figure 2025023457000002
    Figure 2025023457000002
  • Figure 2025023457000003
    Figure 2025023457000003
Patent Text Reader

Abstract

To provide a polyester film which is reduced in coloration of a film while securing process stability, and a method for producing the same.SOLUTION: A polyester film has a base material layer containing a polyester resin as a main component, wherein the polyester resin has a linear oligomer content of 100 ppm or less, contains a germanium element, and satisfies the following expression (I). Expression (I): 5 ppm≤germanium element content (mass basis)≤80 ppm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film having little coloration. [Background technology]

[0002] Polyester films have excellent mechanical properties, thermal properties, chemical resistance, electrical properties, and moldability, and are used in a variety of applications. Among polyester films, polyethylene terephthalate (hereinafter sometimes referred to as PET) films in particular have excellent transparency and processability, and are therefore ideally used as highly transparent optical films, particularly for displays and touch panels.

[0003] Generally, polyester resins, and PET in particular, are produced by producing an esterification product from a dicarboxylic acid such as terephthalic acid or an ester-forming derivative thereof and ethylene glycol or a glycol mainly composed of ethylene glycol, and then polycondensing the esterification product at high temperature and high vacuum in the presence of a polycondensation catalyst.

[0004] Germanium compounds, titanium compounds, antimony compounds, etc. have been used as polycondensation catalysts for producing polyester resins, but antimony compounds, which are inexpensive and have excellent catalytic activity, are the most widely used. However, when antimony compounds are used as polycondensation catalysts, they tend to precipitate as insoluble metal particles during the production stage of polyester resins, which causes defects when the obtained polyester resin is molded into a film, and the antimony compounds induce fine gelled matter during melt extrusion.

[0005] In addition, when antimony compounds are used as polycondensation catalysts, the decomposition reaction of polyester resins tends to generate and increase linear oligomers such as polyester resin monomer components and low molecular weight substances (oligomer components). These linear oligomers volatilize and scatter during the manufacturing process, molding, and processing, and can cause contamination of the surface of molded products such as films, or cause process contamination. These contaminations can lead to a deterioration in the quality of the final molded products.

[0006] Furthermore, when antimony compounds or titanium compounds are used as polycondensation catalysts, polyester resins tend to yellow or become colored, making it difficult to obtain highly transparent films. In recent years, the quality requirements for highly transparent films, especially for optical applications, have been increasing, and there is a demand for technology that can improve the above-mentioned problems while maintaining mechanical and thermal properties.

[0007] In response to these problems, the following studies have been carried out. For example, Patent Document 1 discloses a technique for reducing streaks caused by a die by setting the component ratio of linear oligomers within a specific range, thereby ensuring process stability in the film manufacturing process. Patent Document 2 discloses a technique for reducing the amount of linear oligomers generated by incorporating specific amounts of antimony, manganese, and sodium, thereby ensuring process stability in the film manufacturing process. Patent Document 3 discloses a technique for reducing the amount of linear oligomers generated by controlling the die temperature to be lower than the melting point of the polyester resin, thereby ensuring process stability in the film manufacturing process. Patent Document 4 discloses a technique for removing linear oligomers on the film surface by performing a solvent treatment, a corona discharge treatment, a plasma discharge treatment, a flame treatment, or the like during the film manufacturing process, thereby ensuring process stability in the film manufacturing process. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2018 / 092414 [Patent Document 2] JP 2019-85504 A [Patent Document 3] Japanese Patent Application Publication No. 10-180844 [Patent Document 4] JP 2001-89590 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, the method described in Patent Document 1 can suppress the occurrence of die streaks to a certain degree, but cannot suppress contamination of process rolls such as cast drums and longitudinal stretching rolls, and thus has a problem of not being able to ensure sufficient process stability. The methods described in Patent Documents 2 and 3 can reduce the amount of linear oligomers generated to a certain degree, and have an effect of improving process stability, but have a problem of not being able to sufficiently suppress yellowing and coloring of the film. The method described in Patent Document 4 requires a new treatment step to be added during the film production process, making it difficult to apply to existing equipment, and also has a problem of not being able to sufficiently suppress yellowing and coloring of the film.

[0010] An object of the present invention is to solve these problems and to provide a polyester film that is less colored while ensuring process stability during production. [Means for solving the problem]

[0011] The present invention aims to solve the above problems. (1) A polyester film having a base layer containing a polyester resin as a main component, the base layer having a linear oligomer content of 5 ppm or more and 100 ppm or less, and the base layer satisfying the following formula (I): 5ppm≦Germanium element content (by mass)≦80ppm (I) (2) The polyester film according to (1), wherein the base layer satisfies all of the following formulae (II) to (IV): 5ppm≦Manganese element content (by mass)≦40ppm (II) 4ppm≦Sodium content (by mass)≦40ppm (III) 5ppm≦Metal element content (mass basis)≦100ppm (IV) (3) The polyester film according to (1) or (2), wherein the base layer satisfies the following formula (V): 15ppm≦Phosphorus element content (mass basis)≦70ppm (V) (4) The polyester film according to (3), wherein at least a part of the phosphorus element is derived from phosphoric acid and sodium phosphate. (5) The polyester film according to any one of (1) to (4), wherein the base layer has a melt resistivity of 10.0 MΩ·cm or less. (6) The polyester film according to any one of (1) to (5), which has a coating layer on at least one surface of the base layer. (7) The polyester film according to any one of (1) to (6), having an internal haze of 0.5% or less. Effect of the Invention

[0012] According to the present invention, it is possible to provide a polyester film which is less colored while ensuring process stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The polyester film of the present invention is described in detail below. The polyester film of the present invention is characterized in that it has a base layer mainly composed of a polyester resin, the base layer has a linear oligomer content of 5 ppm or more and 100 ppm or less, and the base layer satisfies the following formula (I): 5 ppm≦Germanium element content (by mass)≦80 ppm (I).

[0014] The polyester film of the present invention has a base layer mainly composed of a polyester resin. In the present invention, the polyester resin refers to a resin having a molecular structure in which dicarboxylic acid units and diol units are repeatedly linked by ester bonds, and the polyester film refers to a sheet-shaped molded body mainly composed of a polyester resin. Details of polyester resins that can be suitably used for the polyester film of the present invention will be described later. The main component refers to a component that is contained in an amount of more than 50 mass% to 100 mass% or less when the total components of the target object are taken as 100 mass%. The base layer mainly composed of a polyester resin refers to a layer that is mainly composed of a polyester resin and has a thickness of 10 μm or more (hereinafter, the "base layer mainly composed of a polyester resin" may be simply referred to as the "base layer"). The base layer may have a single layer structure or a laminate structure, and when layers that satisfy the above requirements are laminated in succession, the entirety of these layers is treated as one base layer.

[0015] In the polyester film of the present invention, the linear oligomer content in the base layer is required to be 5 ppm or more and 100 ppm or less from the viewpoint of stabilizing the manufacturing process and reducing coloration. The upper limit is preferably 80 ppm, more preferably 65 ppm, further preferably 25 ppm, and particularly preferably 15 ppm. In addition, the lower limit is substantially 5 ppm from the viewpoint of the linear oligomer generation mechanism.

[0016] In the present invention, the linear oligomer refers to a monomer component or oligomer component generated by decomposition reactions such as thermal decomposition, hydrolysis, and oxidative decomposition of polyester resin, specifically, a dicarboxylic acid component constituting polyester resin, or a chain reaction product generated by the reaction of a carboxyl group of a dicarboxylic acid with a hydroxyl group of a diol, and does not include cyclic oligomers such as cyclic trimers. For example, in the case of PET, a typical polyester resin, terephthalic acid (TPA), monohydroxyethyl terephthalate (MHET), which is a reaction product of terephthalic acid and ethylene glycol, and bishydroxyethyl terephthalate (BHET), etc. are generated as linear oligomers.

[0017] Generally, linear oligomers tend to sublime and precipitate, and therefore in the film production process, they are released into the atmosphere at high temperatures during melt extrusion and diffuse into the air, or they seep out from the inside of the film to the surface, causing contamination of the die and casting drum, or contamination of the film and roll, etc. This leads to a decrease in the productivity of polyester films and deterioration in quality, such as scratches on the film.

[0018] By setting the linear oligomer content within the above range, process stains and film stains in the film production process can be reduced, the frequency of cleaning in the film production process can be reduced, and the process stability can be improved, and the occurrence of film scratches and coloring due to process stains can be reduced, resulting in a high-quality polyester film. The method for measuring the linear oligomer content in the base layer will be described in detail later.

[0019] The method for making the linear oligomer content within the above range is not particularly limited, and for example, a method of reducing the linear oligomer content by previously subjecting the polyester resin as a raw material to solid-phase polymerization, a method of thoroughly drying before feeding into an extruder, a method of using a polyester resin with a small amount of carboxyl groups at the end, a method of suppressing hydrolysis during melt extrusion by adding a terminal blocking agent, a method of lowering the melt extrusion temperature or the die temperature, a method of melt extrusion under an inert gas atmosphere or under reduced pressure, etc. can be adopted. In addition to these methods, it is also preferable to adopt a polyester resin that is produced by the method described below and is unlikely to generate linear oligomers. Note that these methods can be used in appropriate combination.

[0020] The base layer in the polyester film of the present invention must contain germanium element in an amount of 5 ppm to 80 ppm by mass. The lower limit is preferably 10 ppm. The upper limit is preferably 60 ppm, more preferably 50 ppm. The germanium compound is used as a polymerization catalyst for polyester resin, and by setting the amount to the above lower limit or more, it is possible to proceed with the polycondensation reaction without delay, and the occurrence of coloring can be reduced. In addition, the germanium element has excellent catalytic activity, and if it is present in excess, it contributes to thermal decomposition, oxidative decomposition, and hydrolysis of the polyester resin. Therefore, by satisfying the amount of germanium element below the above upper limit, it is possible to suppress various decompositions of the polyester resin, and as a result, the linear oligomer content can also be reduced. The method for measuring the amount of germanium element in the base layer will be described later (the same applies to the amounts of other elements). Here, the mass basis means that the total components constituting the polyester film are used as the basis, and can be interpreted in the same manner hereinafter.

[0021] The base layer in the polyester film of the present invention preferably contains manganese element in an amount of 5 ppm to 40 ppm by mass. The lower limit is more preferably 10 ppm. The upper limit is more preferably 30 ppm. Since manganese compounds affect the thermal decomposition of polyester resins, the heat resistance of polyester films can be improved and coloring can be easily reduced by making the amount of manganese equal to or greater than the lower limit. In addition, manganese element has high catalytic activity even in heat treatment at a relatively low temperature below the melting point of polyester resins, such as in a film stretching process, and contributes to thermal decomposition, oxidative decomposition, and hydrolysis of polyesters. Therefore, by satisfying the amount of manganese element equal to or less than the upper limit, various decompositions of polyester resins and films in processing steps and the associated coloring can be easily suppressed.

[0022] The base layer in the polyester film of the present invention preferably contains sodium element in an amount of 4 ppm or more and 40 ppm or less by mass. The upper limit is more preferably 30 ppm, and even more preferably 20 ppm. By keeping the sodium element in the above range, the generation of foreign matter caused by sodium element is reduced, heat resistance is improved, and various decompositions of the polyester resin and film caused by thermal decomposition and the associated coloring are easily suppressed.

[0023] In addition, the base layer in the polyester film of the present invention preferably has a metal element content of 5 ppm or more and 100 ppm or less, more preferably 80 ppm or less, based on mass. If the amount of metal elements in the base layer exceeds 100 ppm, the polyester chain is promoted to be cut in the melt extrusion process, so that gelled matter having a three-dimensional structure is likely to occur frequently, which may cause defects in the film and reduce the quality. In addition, the metal component itself or a complex of the metal component and other chemical substances may precipitate, which may increase defects in the film. The metal element here is synonymous with the metal element generally defined, and refers to all elements in Groups 1 and 2 to 12 of the periodic table of elements except hydrogen, Groups 13 from the third period onwards except boron, Groups 14 from the fourth period onwards except carbon and silicon, Groups 15 from the fifth period onwards, and Group 16 of the sixth period. The lower limit of the metal element content in the base layer of the polyester film is substantially 5 ppm from the lower limit of the germanium element content, and when manganese element or sodium element is contained in addition to germanium element, it is preferable that the lower limit of the metal element content is 14 ppm from the lower limit of the content of these elements.

[0024] The base layer in the polyester film of the present invention preferably contains phosphorus element in an amount of 15 ppm or more and 70 ppm or less by mass. The lower limit is more preferably 20 ppm, even more preferably 25 ppm, and particularly preferably 30 ppm. The upper limit is more preferably 60 ppm, and even more preferably 50 ppm. By setting the content within the above range, heat resistance can be imparted to the polyester film, and the productivity can also be easily improved.

[0025] The base layer of the polyester film of the present invention is free from metal elements that are likely to cause foreign matter, and is easy to impart heat resistance to the polyester by adding a compound containing manganese and sodium elements or a phosphorus compound. In particular, for sodium and phosphorus elements, phosphoric acid and sodium phosphate are preferably used from the viewpoint of suppressing deterioration of the polyester resin. That is, in the polyester film of the present invention, it is more preferable that at least a part of the phosphorus element contained in the base layer is derived from at least one of phosphoric acid and sodium phosphate. Note that, when phosphate ions and sodium ions or sodium phosphate are present in the base layer, the phosphorus element contained in the base layer is considered to be "derived from at least one of phosphoric acid and sodium phosphate".

[0026] In order to enhance the effect of suppressing deterioration (hydrolysis resistance) of the polyester resin of the base layer, it is preferable to add phosphoric acid and sodium phosphate to the polyester resin that is the raw material of the base layer, and it is more preferable to make the contents of these components closer to equal amounts in terms of molar ratio. That is, in the polyester film of the present invention, it is preferable that the base layer contains both phosphorus element derived from phosphoric acid and phosphorus element derived from sodium phosphate, and it is more preferable to make the amounts of both closer to equal amounts in terms of molar ratio. By adopting such an embodiment, it is possible to reduce the coloration of the polyester film due to the deterioration of the polyester resin.

[0027] In the polyester film of the present invention, from the viewpoint of achieving both reduction of thickness unevenness of the polyester film and improvement of productivity, the melt resistivity of the base layer is preferably 10.0 MΩ·cm or less. One of the factors that affect the thickness unevenness of the polyester film obtained by the melt casting method is the electrostatic applicability when the molten sheet-like material for obtaining the base layer is cooled and solidified on a cast drum. This electrostatic applicability can be evaluated by the melt resistivity when the base layer of the finally obtained polyester film is melted, and can also be substituted by the melt resistivity of the molten polyester resin that is the raw material of the base layer.

[0028] The melt resistivity is the volume resistivity of the heat-melted polyester film (or polyester resin). From the above viewpoint, the melt resistivity of the base layer of the polyester film of the present invention is preferably 10.0 MΩ·cm or less, more preferably 5.0 MΩ·cm or less. When the melt resistivity of the base layer is 10.0 MΩ·cm or less, the electrostatic applicability is good during cooling and solidification in the cast drum, so that the thickness unevenness of the obtained polyester film is suppressed, and the film production speed can be increased to improve productivity. In addition, the lower limit of the melt resistivity of the base layer is not particularly limited, but is 0.1 MΩ·cm from the viewpoint of feasibility. The melt resistivity of the base layer of the polyester film can be measured by the following method (the details of the measurement method will be described later). First, the crushed polyester film (if it has a coating layer, the coating layer is removed and then crushed) is vacuum-dried at 180°C for 3 hours, and then melted at 290°C. Then, an electrode is made by placing a Teflon (registered trademark) spacer between two copper plates, and this electrode is immersed in the obtained molten resin. A voltage of 5000 V (V) is applied between the electrodes, and the voltage (V') is measured. The melt resistivity value (ρ) is calculated using the following formula. ρ(Ω cm)=V S R / (I V') In the formula, V is the applied voltage (V), S is the electrode area (cm 2 ), R: resistor resistance (Ω), I: distance between electrodes (cm), V': measured voltage (V).

[0029] The method of making the melt resistivity of the base layer within the above range includes, but is not limited to, making the metal element content or phosphorus element content in the polyester resin, which is the raw material of the base layer, within the above-mentioned preferred range, and adding particles or compounds responsible for electrical conduction to the raw material. However, if the metal element content in the raw material is increased, as described above, the heat resistance of the resulting polyester film may be reduced or foreign matter may be generated due to gelation. Therefore, it is preferable to apply an ionic substance that is not based on metal, and for example, sulfonium compounds, phosphonium compounds, ammonium compounds, imidazolium compounds, pyridinium compounds, and pyrrolidinium compounds can be selected as cationic substances, and sulfonate compounds, phosphate compounds, sulfate compounds, acetate compounds, imide compounds, and the like can be selected as anionic substances. In particular, neutralized salts of phosphonium compounds and sulfonate compounds are preferable.

[0030] The polyester resin, which is the main component of the base layer in the polyester film of the present invention, is preferably polyethylene terephthalate (PET) in order to sufficiently increase heat resistance. In addition, a copolymer component may be contained within a range that does not impair the effects of the present invention. Polyethylene terephthalate refers to a polyester resin whose main structural unit is an ethylene terephthalate unit, and the main structural unit refers to a structural unit contained in more than 50 mol% when all structural units constituting the molecular chain of the resin are 100 mol%. Note that the same can be interpreted for other polyester resins below, except that the main structural unit is replaced.

[0031] Next, a method for producing the polyester resin used in the base layer of the polyester film according to the present invention will be described. The method for producing the polyester resin uses a dicarboxylic acid component or its ester and a diol component as main raw materials and consists of the following two-stage process: (A) an esterification reaction or (B) an ester exchange reaction as the first stage, followed by (C) a polycondensation reaction as the second stage.

[0032] As raw materials for producing the polyester resin used in the base layer of the polyester film of the present invention, dicarboxylic acids or dicarboxylic acid esters and diols can be used, and these can also be used in combination of two or more kinds.

[0033] Examples of dicarboxylic acid components that can be used in the production of polyester resins include terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, diphenyl-4,4'-dicarboxylic acid, 5-sodium sulfoisophthalic acid, oxalic acid, succinic acid, adipic acid, sebacic acid, malonic acid, and dimer acid. Examples of dicarboxylic acid esters include the lower alkyl esters, acid anhydrides, and acyl chlorides of the above-mentioned dicarboxylic acids, and methyl esters, ethyl esters, and hydroxyethyl esters are preferably used. These components may be used alone or in combination.

[0034] In the polyester resin used in the base layer of the polyester film of the present invention, more preferred embodiments of the dicarboxylic acid or dicarboxylic acid ester are terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, or their alkyl esters, since they can give polyester resins that have high melting points and are easy to process into films, and these can also be used in appropriate combinations.

[0035] Examples of diols that can be used in the production of polyester resins include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, butanediol, 2-methyl-1,3-propanediol, hexanediol, and neopentyl glycol; alicyclic diols include saturated alicyclic primary diols such as cyclohexanedimethanol, cyclohexanediethanol, norbornanedimethanol, norbornanediethanol, tricyclodecanedimethanol, tricyclodecanediethanol, decalindimethanol, and decalindiethanol; and saturated heterocyclic primary diols containing cyclic ethers such as isosorbide. Other examples include various alicyclic diols such as cyclohexanediol, bicyclohexyl-4,4'-diol, 2,2-bis(4-hydroxycyclohexylpropane), 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, cyclopentanediol, 3-methyl-1,2-cyclopentadiol, 4-cyclopentene-1,3-diol, and adamantanediol, and aromatic diols such as paraxylene glycol, bisphenol A, bisphenol S, styrene glycol, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, and 9,9'-bis(4-hydroxyphenyl)fluorene.

[0036] These components may be used alone or in combination, and polyfunctional alcohols such as trimethylolpropane and pentaerythritol may also be used other than the diol within the scope of not impairing the effects of the present invention. It is preferable to use ethylene glycol as the diol, since it is possible to fully achieve the effects of the present invention and to obtain a polyester resin that is easily processed into a film.

[0037] In the manufacturing method of the polyester resin used in the base layer of the polyester film of the present invention, the (A) esterification reaction step in the first step is a step of esterifying a dicarboxylic acid with a diol at a predetermined temperature until a predetermined amount of water is distilled to obtain a low polymer. When obtaining a low polymer by esterification reaction, the molar ratio of dicarboxylic acid to diol (diol / dicarboxylic acid) before the start of esterification reaction is preferably in the range of 1.05 to 1.40 from the viewpoint of esterification reactivity and heat resistance. More preferably, it is 1.05 to 1.30, and even more preferably, it is 1.05 to 1.20. By setting it in the above range, it has good reactivity and can suppress the generation of by-products such as dimers of diol, so that the heat resistance of the obtained polyester resin can be improved.

[0038] The (B) transesterification step is a step of transesterifying a dicarboxylic acid alkyl ester with a diol until a predetermined amount of alcohol is distilled to obtain a low polymer. When a low polymer is obtained by transesterification, the molar ratio of the dicarboxylic acid alkyl ester to the diol (diol / dicarboxylic acid alkyl ester) is preferably in the range of 1.7 to 2.3 from the viewpoints of reactivity and heat resistance. By setting the ratio in the above range, the transesterification reaction can be efficiently progressed and the by-production of a dimer of the diol can be suppressed, thereby improving the heat resistance.

[0039] In the second step, the polycondensation reaction (C) is a step for obtaining a polyester resin from the low polymer obtained by the esterification reaction (A) or the transesterification reaction (B).

[0040] The polyester resin used in the base layer of the polyester film of the present invention can be produced by any of batch polymerization, semi-continuous polymerization, and continuous polymerization.

[0041] In the method for producing the polyester resin used in the base layer, the catalyst used in the (A) esterification reaction may be a compound such as manganese, cobalt, zinc, titanium, or calcium, but it is preferable to carry out the esterification reaction without a catalyst from the viewpoint of thermal decomposition and generation of foreign matter in the polycondensation reaction stage. Here, the (A) esterification reaction proceeds sufficiently even without a catalyst due to the autocatalytic action of the carboxylic acid. In addition, a known transesterification catalyst can be used as the catalyst used in the (B) transesterification reaction. Examples of the transesterification catalyst include organic manganese compounds, organic magnesium compounds, organic calcium compounds, organic cobalt compounds, and organic lithium compounds, and specific examples thereof include carbonates, acetates, benzoates, oxides, and hydroxides, but are not limited thereto.

[0042] In the manufacturing method of the polyester resin used in the base layer of the polyester film of the present invention, the compound containing germanium, manganese, and sodium may be added at any stage of the (A) esterification reaction or (B) ester exchange reaction process, or the subsequent (C) polycondensation reaction process. However, by adding the compound before the end of the polycondensation reaction, it is possible to obtain a polyester resin having improved heat resistance and reduced foreign matter.

[0043] In the method for producing the polyester resin used in the base layer of the polyester film of the present invention, it is preferable to add a compound containing germanium element (more preferably a compound containing manganese element and sodium element in addition thereto) before the end of the polycondensation reaction, and the content of the compound satisfies the following formula (VI) ((VI) to (VIII) when the compound containing manganese element and sodium element is included) with respect to the finally obtained polyester resin. By adopting such an embodiment, it becomes easy for the base layer of the obtained polyester film to satisfy the formula (I) ((I) to (IV) when the compound containing manganese element and sodium element is included). In addition, when the base layer is produced by mixing another resin with the polyester resin, in the following formulas (VI) to (VIII), "mass ratio to polyester resin" is interpreted as "mass ratio to polyester resin composition for producing base layer". 5ppm≦Germanium content (mass ratio to polyester resin)≦80ppm (VI) 5ppm≦Manganese element content (mass ratio to polyester resin)≦40ppm (VII) 4 ppm or less sodium element content (mass ratio to polyester resin) ≦ 40 ppm (VIII).

[0044] In the method for producing the polyester resin used in the base layer of the polyester film of the present invention, it is necessary to add germanium element so that the content is 5 ppm or more and 80 ppm or less relative to the mass of the polyester resin. The lower limit is preferably 10 ppm. The upper limit is preferably 60 ppm, more preferably 50 ppm. The germanium compound is used as a polymerization catalyst for polyester, and by making it above the above lower limit, it is possible to proceed with the polycondensation reaction without delay. In addition, the germanium element has excellent catalytic activity, and if it is present in excess, it contributes to thermal decomposition, oxidative decomposition, and hydrolysis of polyester. Therefore, by satisfying the amount of germanium element below the above upper limit, it is possible to suppress various decompositions of polyester. Examples of compounds containing germanium element used in the production of polyester resin include, but are not limited to, germanium oxide and germanium alkoxide. It is possible to use these compounds alone or in combination of multiple types.

[0045] The polyester resin used in the base layer of the polyester film of the present invention preferably contains manganese element in an amount of 5 ppm or more and 40 ppm or less relative to the mass of the polyester resin. The lower limit is more preferably 10 ppm. The upper limit is more preferably 30 ppm. By making the manganese element amount equal to or more than the above lower limit, the heat resistance of the polyester resin is easily improved. In addition, the manganese element has high catalytic activity even in heat treatment at a relatively low temperature below the melting point of the polyester resin, such as in the film stretching process, and contributes to thermal decomposition, oxidative decomposition, and hydrolysis of the polyester. Therefore, by satisfying the above upper limit or less of the manganese element amount, it is easy to suppress various decompositions of the polyester resin in the processing process into the polyester film and the associated coloring of the polyester film.

[0046] The compound containing manganese element used in the manufacture of the polyester resin used in the base layer of the polyester film of the present invention is not particularly limited, but examples thereof include manganese acetate, manganese nitrate, manganese chloride, manganese sulfate, and their hydrates, and manganese acetate is preferred from the viewpoint of solubility and catalytic activity. These compounds can be used alone or in combination of multiple types. The form of the compound containing manganese element when added may be any of powder, slurry, and solution, and it is preferable to add it as a solution from the viewpoint of dispersibility. The solvent at this time is preferably the same as the diol component of the polyester resin. For example, in the case of PET, it is particularly preferable to use ethylene glycol as the solvent.

[0047] The polyester resin used in the base layer of the polyester film of the present invention preferably contains sodium element in an amount of 4 ppm or more and 40 ppm or less relative to the mass of the polyester resin. The upper limit is more preferably 30 ppm, and even more preferably 20 ppm. If the sodium element content exceeds 40 ppm, metal aggregate foreign matter may increase and the heat resistance of the polyester resin may deteriorate. If the sodium element content is below 4 ppm, the heat resistance of the polyester resin may deteriorate. By setting the sodium element content within the above range, the heat resistance is improved, and the deterioration of the polyester resin caused by thermal decomposition during the production of the polyester film and the associated coloring of the polyester film are easily suppressed.

[0048] The compound containing sodium element used in the production of the polyester resin used in the base layer of the polyester film of the present invention is not particularly limited. For example, sodium phosphate, hydroxide, acetate, carbonate, nitrate, chloride, etc. can be used. From the viewpoint of heat resistance, the compound containing sodium element is more preferably sodium phosphate. Examples of sodium phosphate include sodium dihydrogen phosphate, disodium hydrogen phosphate, and trisodium phosphate. From the viewpoint of heat resistance, sodium dihydrogen phosphate is particularly preferable. In addition, multiple sodium phosphates may be used in combination.

[0049] In the production of the polyester resin used in the base layer of the polyester film of the present invention, it is preferable to use the above-mentioned sodium phosphate in combination with another compound containing phosphorus, and it is particularly preferable to mix them as a buffer solution containing sodium phosphate and phosphoric acid. By adding the buffer solution containing sodium phosphate and phosphoric acid, it is possible to develop better heat resistance.

[0050] In addition, an alkali metal compound other than sodium phosphate may be used in combination within the range of the above-mentioned sodium element content. For example, by using potassium hydroxide in combination, the melt resistivity of polyester required for electrostatic application film formation in film production can be reduced, thereby improving productivity.

[0051] The sodium-containing compound may be added in the form of powder, slurry, or solution, and is preferably added as a solution from the viewpoint of dispersibility. The solvent used in this case is preferably the same as that of the diol component of the polyester resin, and in the case of PET, ethylene glycol is particularly preferred.

[0052] The polyester resin used in the base layer of the polyester film of the present invention is preferably added with phosphorus element so that the content is 15 ppm or more and 70 ppm or less relative to the mass of the polyester resin. The lower limit is more preferably 20 ppm, and even more preferably 25 ppm. The upper limit is more preferably 60 ppm, and even more preferably 50 ppm. By setting it in the above range, it is easy to impart heat resistance to the polyester resin.

[0053] In the method for producing the polyester resin used in the base layer of the polyester film of the present invention, it is preferable to further deactivate the polyester resin obtained after the polycondensation reaction. It is known that the catalytic activity of the polyester resin obtained by polycondensation reaction using a germanium catalyst is deactivated by treating it under relatively mild conditions such as hot water. By losing the catalytic activity, when the polyester resin is used in the subsequent film formation process, the thermal decomposition caused by the polycondensation catalyst is suppressed, and it is easy to obtain a polyester film with excellent heat resistance.

[0054] The deactivation treatment of the polyester resin used in the base layer of the polyester film of the present invention can be carried out with various solutions such as water, phosphorus compounds, and ammonia compounds. Examples of phosphorus compounds include, but are not limited to, phosphate esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, dimethyl phosphate, diphenyl phosphate, methyl phosphate, and ethyl phosphate, and aqueous solutions or solutions of phosphorus compounds such as phosphoric acid and polyphosphoric acid, and the polyester resin is contacted with the phosphorus compounds. Examples of ammonia compounds include triethylamine, tetraethylammonium hydroxide, and tetra-n-butylammonium hydroxide. The temperature at which the polyester resin is contacted with these treatment solutions and treated is preferably 20°C or higher and 120°C or lower, more preferably 40°C or higher and 100°C or lower, and even more preferably 50°C or higher and 100°C or lower. The treatment time is preferably 30 minutes or higher and 24 hours or lower, and more preferably 1 hour or higher and 12 hours or lower.

[0055] In the method for producing the polyester resin used in the base layer of the polyester film of the present invention, for example, germanium element and phosphorus element are distilled off during the polycondensation reaction, so it is preferable to adjust the addition amount taking into consideration the distilled amount so as to obtain the above-mentioned element amount.

[0056] In the method for producing the polyester resin used in the base layer of the polyester film of the present invention, when the method is carried out via (A) esterification reaction, it is preferable to add a glycol component such as ethylene glycol after the esterification reaction and before adding a compound containing sodium element. More preferably, it is added after the compound containing manganese element and before adding a compound containing sodium element. Since the low molecular weight polyester resin obtained by the esterification reaction has a higher degree of polymerization than the low molecular weight polyester resin obtained by the transesterification reaction, it is difficult to disperse and is prone to foreign matter formation when sodium phosphate is used. Therefore, foreign matter formation can be suppressed by adding a glycol component such as ethylene glycol and lowering the degree of polymerization by depolymerization. At this time, depolymerization can be more efficiently performed if a compound containing manganese element is present.

[0057] The amount of glycol components such as ethylene glycol to be added is preferably 0.05 to 0.5 times by mol relative to the total amount of acid components, and more preferably 0.1 to 0.3 times by mol. By adjusting the amount within the above range, the polymerization time is not delayed due to a temperature drop in the polymerization system, and the sodium phosphate salt can be prevented from becoming a foreign substance.

[0058] It is preferable to stir the reaction system during and after the addition of the compounds containing germanium, manganese, and sodium, as stirring can disperse the additives more uniformly.

[0059] The polyester resin used in the base layer of the polyester film of the present invention preferably has a linear oligomer content of 5 ppm or more and 100 ppm or less. The upper limit is more preferably 80 ppm, further preferably 50 ppm, and particularly preferably 30 ppm, and the lower limit is substantially 5 ppm from the viewpoint of the linear oligomer generation mechanism. By setting the linear oligomer content within the above range, it is easy to control the linear oligomer content of the base layer of the polyester film. As a method for setting the linear oligomer content of the polyester resin within the above range, it is preferable to adopt a polyester resin that is produced by the above-mentioned method and is unlikely to generate linear oligomers. The details of the method for measuring the linear oligomer content of the polyester resin will be described later.

[0060] The polyester resin used in the base layer of the polyester film of the present invention preferably has a b-value of 12.0 or less, more preferably 10.0 or less, and even more preferably 7.0 or less. By setting the b-value of the polyester resin within the above range, the transparency of the polyester film can be easily ensured, and it can be preferably used for optical applications where high transparency is often required. From the viewpoint of the molecular structure of the polyester resin, the lower limit is essentially 3.0. As a method for setting the b-value of the polyester resin within the above range, it is preferable to adopt a polyester resin that is not easily thermally decomposed and is produced by the method described above. The details of the method for measuring the b-value of the polyester resin will be described later.

[0061] In the method for producing the polyester resin used in the base layer of the polyester film of the present invention, solid-phase polymerization may be performed to obtain a polyester resin having a high molecular weight. The solid-phase polymerization is performed by heating the polyester resin under an inert gas atmosphere or under reduced pressure, although the apparatus and method are not particularly limited. The inert gas may be any gas inert to the polyester resin, such as nitrogen, helium, and carbon dioxide, but nitrogen is preferably used from the viewpoint of economy. In addition, under reduced pressure conditions, it is advantageous to achieve a higher vacuum because it shortens the time required for the solid-phase polymerization reaction, and specifically, it is preferable to maintain the pressure at 110 Pa or less. In addition, when performing a deactivation treatment, it is preferable to perform it after the solid-phase polymerization in order to perform the solid-phase polymerization efficiently.

[0062] When the polyester resin used in the base layer of the polyester film of the present invention is processed into the base layer of the polyester film, one or more of various additives, such as colorants including pigments and dyes, lubricants, antistatic agents, flame retardants, ultraviolet absorbers, antibacterial agents, nucleating agents, plasticizers, and release agents, may be added to the polyester resin within a range that does not impair the effects of the present invention.

[0063] Specific examples of polyester resins used in the base layer of the polyester film of the present invention and methods for producing the base layer using the same will be given below, but the present invention is not limited thereto.

[0064] A slurry of terephthalic acid and ethylene glycol (1.15 times the molar amount of terephthalic acid) is gradually added to an esterification reactor containing dissolved bishydroxyethyl terephthalate (BHT) at 245-260°C to allow the esterification reaction to proceed. The temperature in the reaction system is controlled to 245-250°C, and the esterification reaction is terminated when the reaction rate reaches 95%.

[0065] The esterification product thus obtained is transferred to a polymerization apparatus, and a manganese compound and a germanium compound are added. Then, ethylene glycol is added, and phosphoric acid and sodium phosphate are added. During these operations, it is preferable to keep the temperature in the system at 240 to 255°C so that the esterification product does not solidify.

[0066] Thereafter, the temperature inside the polymerization apparatus is gradually raised to 285-295°C, while the pressure inside the polymerization apparatus is gradually reduced from normal pressure to 133 Pa or less to distill off ethylene glycol. The reaction is terminated when a predetermined stirring torque is reached, the reaction system is returned to normal pressure with nitrogen gas, and the molten polyester is discharged into cold water in the form of strands and cut to obtain a polyester resin.

[0067] The polyester resin thus obtained has excellent heat resistance and produces little gel composition or low molecular weight substances such as terephthalic acid during melt molding or processing, and can be suitably used for polyester films that require high quality, particularly for optical film applications, i.e., the base layer of the polyester film of the present invention.

[0068] The base layer in the polyester film of the present invention is not particularly limited as long as it is mainly composed of polyester resin, but is preferably a biaxially oriented polyester film. The term "biaxial orientation" as used herein refers to a film that shows a biaxially oriented pattern in wide-angle X-ray diffraction. A biaxially oriented polyester film can generally be obtained by stretching an unstretched polyester sheet by about 2.5 to 5.0 times in each of the longitudinal and transverse directions of the sheet, and then subjecting the sheet to heat treatment to complete the crystal orientation. The longitudinal direction refers to the direction in which the film runs during the manufacturing process (in the case of a film roll, this corresponds to the winding direction, also called the vertical direction), and the transverse direction (also called the horizontal direction) refers to the direction perpendicular to the longitudinal direction within the film plane.

[0069] The base layer of the polyester film of the present invention is obtained by melt-extruding a resin composition mainly composed of a polyester resin and forming it into a sheet. The base layer of the polyester film of the present invention may be composed of one layer in the thickness direction, or may have multiple layers. A base layer having multiple layers can be obtained, for example, by supplying molten polyester resin from multiple extruders, stacking them in the thickness direction, and then cooling and solidifying them to form a sheet.

[0070] Optical films used in displays and the like have various processing such as a hard coat layer, an electrode layer, a refractive index adjustment layer, and a transparent adhesive layer on their surfaces, so that the external haze, which is scattering due to the surface shape, can be adjusted by the processing configuration. On the other hand, the internal haze due to internal scattering cannot be adjusted by processing, so it is a very important characteristic for an optical substrate film. Therefore, when assuming use in optical applications, it is preferable that the internal haze of the polyester film of the present invention is 0.5% or less. By adopting such an embodiment, scattering of light transmitted through the polyester film is reduced, and the transparency and definition are improved when used in displays and the like.

[0071] As a method for adjusting the internal haze to a desired value, a method for preventing the inclusion of foreign matter that scatters light, such as additives, impurities, and air bubbles, inside the film, or a method for properly controlling the crystallinity of the polyester film by biaxial orientation can be used. More specifically, this can be achieved by setting the amount of additives, particularly metal elements such as catalysts, in the polyester resin used in the base layer to 100 ppm or less, preferably 80 ppm or less, or by using a specific catalyst type or phosphorus-based additive in an appropriate amount as described above. In addition, other preferred methods include properly storing and weighing the polyester resin to prevent the inclusion of foreign matter, and performing high-precision filtration with a filtration accuracy of 10 μm or less during the melt extrusion process of the polyester resin. These methods can be used in appropriate combination.

[0072] In the polyester film of the present invention, when additives such as lubricants are used for the purpose of reducing the slip coefficient and improving the handling, it is preferable to reduce the amount of additives as much as possible. As a method for efficiently reducing the slip coefficient with a small amount of additives, it is preferable to localize the additives on the film surface as much as possible. Specifically, a method in which a base layer is configured by laminating multiple layers in the thickness direction and an additive is added only to the layer forming the film surface, or a method in which a coating layer containing an additive is provided on the polyester base layer, etc. can be mentioned. In particular, it is preferable that the polyester film of the present invention has a coating layer on at least one surface of the base layer, since it is possible to relatively easily add functions such as improving adhesion with a functional layer provided on the polyester film and imparting antistatic properties.

[0073] In the polyester film of the present invention, the method for laminating the coating layer is not particularly limited. For example, a so-called off-line coating method can be used in which a coating layer is formed by unwinding a film, coating and drying the film in a separate process from the film production process, or a so-called in-line coating method can be used in which a resin is extruded by an extruder, the resin is formed into a sheet-like film, and coating is performed during the film production process to obtain a coated film in one go.

[0074] It is preferable to add a lubricant to the coating layer of the present invention in order to improve the slipperiness of the film surface and improve the handling. The lubricant used is not particularly limited as long as it does not impair the film properties, but examples thereof include inorganic particles such as colloidal silica, titanium oxide, aluminum oxide, zirconium oxide, calcium carbonate, carbon black, and zeolite particles, and organic particles such as acrylic particles, silicone particles, polyimide particles, "Teflon" (registered trademark) particles, crosslinked polyester particles, crosslinked polystyrene particles, crosslinked polymer particles, and core-shell particles. Any of these particles may be used, or a combination of two or more types may be used. The number average primary particle size of these particles (hereinafter, sometimes simply referred to as the average primary particle size) is preferably within the range of 50 to 1000 nm. Here, the average primary particle size is the average particle size of primary particles defined in JIS H7008 (2002) as particles generated by the growth of a single crystal nucleus. The amount of particles added should be appropriately adjusted and designed depending on the thickness of the lubrication layer, resin composition, average primary particle size, desired lubricity, and application, but is preferably in the range of 0.05 to 8 mass%, and more preferably in the range of 0.1 to 5 mass%, when the total components forming the lubrication layer are taken as 100 mass%.

[0075] The coating layer of the polyester film of the present invention may contain known polyester, acrylic, urethane, epoxy, and other resins, either alone or in combination, in order to provide various functions such as retaining lubricant particles, improving adhesion to other functional layers, and sealing oligomers precipitated from the film. Furthermore, the coating layer may contain a melamine, oxazoline, or carbodiimide crosslinking agent.

[0076] The polyester film of the present invention preferably has an internal haze of 0.5% or less, more preferably 0.3% or less. Haze is a value indicating the proportion of light scattered through the polyester film, and the lower the haze, the less light is scattered, and the polyester film has a more transparent and clear appearance. Light scattering is mainly divided into scattering due to the surface shape of the polyester film (external scattering) and scattering due to additives, impurities, cavities, etc. inside the polyester film (internal scattering), and the scattering ratio due to the former is called external haze, and the scattering ratio due to the latter is called internal haze. The internal haze can be measured using a known haze meter, the details of which will be described later.

[0077] The polyester film of the present invention preferably has a film b value of 12.0 or less, more preferably 10.0 or less, and even more preferably 7.0 or less. A low film b value means less coloring, and if the film b value is 12.0 or less, it is easy to use in applications where high quality requirements for film color tone are required, such as optical film applications and decorative film applications. The film b value can be controlled by keeping the b value of the polyester resin itself, which is the raw material, low. The lower limit of the film b value is 3.0, which is a practical lower limit, from the viewpoint of the molecular structure of the polyester resin. The film b value is measured by the method described in the examples.

[0078] Next, the method for producing the polyester film of the present invention will be explained using an example in which polyethylene terephthalate (PET) is used as the polyester resin forming the base layer, but the polyester film of the present invention is not limited to those produced by the following method.

[0079] PET pellets with an intrinsic viscosity (IV) of 0.500 to 0.800 dl / g (details of the measurement method will be described later) constituting the polyester film for the base layer are dried, fed to an extruder, and melted at 260 to 300°C. Next, after removing foreign matter from the molten resin with a filter, the resin is extruded into a sheet from a T-shaped die, and wrapped around a mirror-finished casting drum with a surface temperature of 10 to 60°C using an electrostatic casting method, and cooled and solidified to produce an unstretched PET film. This unstretched film is stretched 2.5 to 5.0 times in the longitudinal direction between rolls heated to 70 to 100°C to obtain a uniaxially stretched film. Note that some or all of the PET pellets may contain recycled raw materials. In addition, when stretching in the longitudinal direction, the temperature of the uniaxially stretched film may be adjusted by heating from above and below using a radiation heater as necessary.

[0080] A water-based coating agent constituting a coating layer is applied to at least one side of this uniaxially stretched film. Then, the widthwise ends of the uniaxially stretched film coated with the water-based coating agent are held by clips of a tenter device and introduced into a drying zone, where the coating agent is dried and then heated at a temperature of 70 to 150°C, and then continuously stretched 2.5 to 5.0 times in the transverse direction in a heating zone of 70 to 150°C, followed by heat treatment for 5 to 40 seconds in a heating zone of 200 to 240°C, and passing through a cooling zone of 100 to 200°C to obtain a polyester film in which a coating layer is laminated on a substrate layer in which crystal orientation has been completed. During the heat treatment, a 3 to 12% relaxation treatment may be performed as necessary. In the above example, the biaxial stretching is performed by sequential longitudinal and transverse stretching, but the stretching may be performed by simultaneous biaxial stretching, and after longitudinal and transverse stretching, the stretching may be performed again in either the longitudinal or transverse direction. However, in the case of simultaneous biaxial stretching, since it is not possible to apply a water-based coating agent to a uniaxially stretched film, when an in-line coating method is employed, it is advisable to apply a water-based coating agent to an unstretched film.

[0081] Thereafter, both ends in the width direction held by the clips are cut and removed from the obtained polyester film, and the film is cut to a desired width and wound up. Note that the cutting and removal of both ends in the width direction and the cutting to a desired width can be performed by a device capable of cutting a traveling film parallel to the longitudinal direction, such as a known slitter. EXAMPLES

[0082] Next, the present invention will be described in more detail using examples, but the present invention is not limited to these examples.

[0083] [Measurement methods for physical properties and evaluation of various characteristics] Measurement of physical properties and evaluation of various characteristics were carried out by the following methods.

[0084] (1) Linear oligomer content in polyester resin and polyester film (base layer) (unit: ppm) 0.1 g of sample was weighed out, and if the sample was polyester resin, it was heat-treated at 290°C for 6 hours under a nitrogen atmosphere. If the sample was polyester film, it was not heat-treated, but was dissolved in 2 mL of a mixed solution of HFIP (hexafluoro-2-propanol) / chloroform = 1 / 1 (volume), and then 3 mL of chloroform was added, and 40 mL of methanol was gradually added. Then, the solution obtained by filtering through a paper filter (No. 2 manufactured by ADVANTEC) was concentrated and dried, and 0.5 mL of DMF (N,N-dimethylformamide) was added to the residue obtained to dissolve and disperse it, and ethanol was added to make a constant volume of 5 mL. Then, the obtained solution was filtered through a PTFE membrane filter with a pore size of 0.45 μm to obtain a sample solution. The obtained sample solution was analyzed by LC / UV to measure the contents of TPA (terephthalic acid), MHET (monohydroxyethyl terephthalate), and BHET (bishydroxyethyl terephthalate) in the polyester resin (or polyester film) after melt processing, and the total amount of these was taken as the linear oligomer content. In the case of a polyester film having a coating layer, the coating layer was polished and removed using "Ultra-Precision Polishing Film" (grain size 15000) manufactured by Sankyo Rikagaku Co., Ltd., to expose the base layer and prepare a measurement sample (hereinafter, the same applies to items in which the base layer is the measurement target, unless otherwise specified).

[0085] (2) Quantitative determination of germanium, manganese, phosphorus, sodium, and metal elements in polyester resin and polyester film (base layer) (unit: ppm) 5 g of the sample was placed on a platinum dish, melted and carbonized using an electric heater, and then completely incinerated in an electric furnace (700°C) for 1.5 hours. The incinerated material was then dissolved in 5 mL of concentrated hydrochloric acid, and pure water was added to make a 10% by mass hydrochloric acid solution, which was used as the measurement sample. The above solution was used as the measurement sample and quantitatively analyzed using atomic absorption spectrometry (frame: acetylene-air, acetylene-dinitrogen monoxide for germanium element only). The atomic absorption spectrophotometer used was the "ZA-3300" manufactured by Hitachi High-Tech Science Corporation.

[0086] (3) Intrinsic viscosity (IV) of polyester resin (unit: -) The polyester resin was dissolved in 100 mL of orthochlorophenol (solution concentration C = 1.2 g / mL), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. The viscosity of the solvent was also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula, and the obtained value was taken as the intrinsic viscosity (IV). ηsp / C=[η]+K[η] 2 C (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).)

[0087] (4) Melt resistivity of polyester resin and polyester film base layer (unit: Ω cm) The polyester resin or crushed polyester film was vacuum dried at 180° C. for 3 hours and then melted at 290° C. An electrode was prepared by sandwiching a "Teflon" (registered trademark) spacer between two copper plates, and this electrode was submerged in the molten resin. A voltage of 5000 V (V) was applied between the electrodes, and the voltage (V') was measured, and the melt resistivity (ρ) was calculated from the following formula. ρ(Ω cm)=V S R / (I V') In the formula, V is the applied voltage (V), S is the electrode area (cm 2 ), R: resistor resistance (Ω), I: distance between electrodes (cm), V': measured voltage (V).

[0088] (5) b value of polyester resin (unit: -) Test pieces measuring 100 mm wide x 100 mm long x 1 mm thick were made using an injection molding machine, and the b value was measured using transmitted light using a colorimeter ("ZE 6000" manufactured by Nippon Denshoku Industries Co., Ltd.). The preparation and measurement of the test pieces were repeated three times, and the average of the values ​​obtained was taken as the b value of the resin. Note that a b value of 12.0 or less is considered to be good enough for use in applications where reduced coloring is required.

[0089] (6) Internal haze of polyester film (unit: %) The measurements were performed using a haze meter (HGM-2DP) manufactured by Suga Test Instruments Co., Ltd. A sample of 60 mm x 30 mm was cut out from the polyester film, and the sample was inserted into a quartz cell filled with tetralin and having an optical path length of 1 cm, and the measurement was performed.

[0090] (7) b value of polyester film (unit: -) Polyester films were stacked to a total thickness of 1 mm to form a sample, and the b value was measured using transmitted light with a colorimeter ("SE 2000" manufactured by Nippon Denshoku Industries Co., Ltd.) based on JIS Z 8722 (2000). The sample was prepared and measured three times, and the average of the obtained values ​​was taken as the b value of the polyester film.

[0091] (8) Process stability While continuously producing polyester film, the film was evaluated once every 4 hours using the method for evaluating the number of scratches described below. 2 When the temperature exceeded 100°C, polyester film production was temporarily interrupted and all process rolls were cleaned. After cleaning, continuous polyester film production was resumed, and the same procedure was repeated until the cumulative polyester film production time reached 240 hours. After that, the average time from the start of polyester film production (restart of production after cleaning) to cleaning was calculated, and the process stability was evaluated according to the following criteria. Note that the polyester film production time was calculated without including the time from interruption to resumption of production.

[0092] <Evaluation method for number of scratches (unit: scratches / m 2 )> 1m 2A polyester film sample was prepared so that the area was 100 mm. In a darkroom, one side of the sample was observed from the light-irradiated side while being illuminated with a 2000 lx LED light (EB-10KM manufactured by OHM) with the incident angle changed in the range of 30° to 150° horizontally relative to the sample, and scratches that could be visually confirmed were sampled. The sampled scratches were observed with a laser microscope, and scratches with a depth of 0.1 μm or more, a length of 0.1 mm or more, and a width of 2 μm or less were counted. The measurement was repeated five times, and the average of the obtained values ​​was taken as the number of scratches. A: The average time from the start of polyester film production to cleaning was more than 48 hours. B: The average time from the start of polyester film production to cleaning was 24 hours or more but less than 48 hours. C: The average time from the start of polyester film production to cleaning was 12 hours or more and less than 24 hours. D: The average time from the start of polyester film production to cleaning was less than 12 hours.

[0093] [Reference Example 1] Preparation of polyester resin 1 A slurry consisting of 86 parts by mass of terephthalic acid and 37 parts by mass of ethylene glycol (1.15 times the molar amount relative to terephthalic acid) was gradually added to an esterification reactor containing 105 parts by mass of bishydroxyethyl terephthalate (hereinafter referred to as BHET) melted at 250°C, and the esterification reaction was allowed to proceed. The temperature in the reaction system was controlled to be 245 to 250°C, and the esterification reaction was terminated when the reaction rate reached 95%.

[0094] 105 parts by mass (corresponding to 100 parts by mass of PET) of BHET was charged in a molten state from the esterification reactor into the polymerization apparatus, and the temperature was set to 255°C. An ethylene glycol solution of manganese acetate tetrahydrate (23 ppm as manganese element relative to the mass of polyester resin) and germanium dioxide (45 ppm as germanium element relative to the mass of polyester resin) were added. Then, an ethylene glycol solution of phosphoric acid (19 ppm as phosphorus element relative to the mass of polyester resin) and sodium dihydrogen phosphate dihydrate (14 ppm as sodium element and 19 ppm as phosphorus element relative to the mass of polyester resin) was added. Then, an ethylene glycol solution of an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide (20 ppm as phosphorus element relative to the mass of polyester resin) was added. Note that germanium dioxide was completely dissolved in a 20% by mass aqueous solution of tetraethylammonium hydroxide, and then an ethylene glycol solution to which ethylene glycol was added was used.

[0095] Thereafter, the temperature inside the polymerization apparatus was gradually increased to 290°C, while the pressure was reduced from normal pressure to 133 Pa or less, and the polymerization reaction was allowed to proceed until a predetermined stirring torque was observed at 290°C. After the polymerization reaction was completed, the reaction system was returned to normal pressure with nitrogen gas, and the molten polyester in the polymerization apparatus was discharged in the form of strands into a water tank, cooled, and then cut to obtain pellet-shaped polyester resin 1. The properties of the obtained polyester resin are shown in Table 1.

[0096] [Reference examples 2~5, 12~17] Polyester resins 2 to 5 and 12 to 17 were obtained in the same manner as in Reference Example 1, except that the amounts of germanium, manganese, sodium, and phosphorus in the polyester resin were adjusted as shown in Tables 1 and 2. The properties of the obtained polyester resins are shown in Tables 1 and 2.

[0097] [Reference examples 6~8] Polyester resins 6 to 8 were obtained in the same manner as in Reference Example 1, except that an ethylene glycol solution containing an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide was not added, and the amount of each component added was changed so that the amount of phosphorus element was as shown in Table 1. The properties of the obtained polyester resins are shown in Table 1.

[0098] [Reference example 9] Polyester resin 9 was obtained in the same manner as in Example 1, except that an ethylene glycol solution of an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide was added, and then an ethylene glycol slurry of colloidal silica having an average particle size of 1 μm was added so that the silica content was 0.002 mass% relative to the polyester resin. The properties of the obtained polyester resin are shown in Table 1.

[0099] [Reference examples 10, 11] Polyester resins 10 and 11 were obtained in the same manner as in Reference Example 1, except that an ethylene glycol solution of tetra-n-butoxytitanium (10 ppm as titanium element relative to the mass of the polyester resin (Reference Example 10)) or an ethylene glycol slurry of diantimony trioxide (70 ppm as antimony element relative to the mass of the polyester resin composition (Reference Example 11)) was added instead of germanium dioxide. The properties of the obtained polyester resins are shown in Table 2.

[0100] [Reference example 18] Polyester resin 18 was obtained in the same manner as in Reference Example 1, except that the ethylene glycol solution of manganese acetate tetrahydrate was not added. The properties of the obtained polyester resin are shown in Table 2.

[0101] [Reference example 19] Polyester resin 19 was obtained in the same manner as in Reference Example 1, except that sodium dihydrogen phosphate dihydrate was not added. The properties of the obtained polyester resin are shown in Table 2.

[0102] [Reference Example 20] Preparation of water-soluble polyester resin (A) for coating Under a nitrogen gas atmosphere, 88 molar parts of terephthalic acid as a dicarboxylic acid component, 12 molar parts of sodium 5-sulfoisophthalate, and 140 molar parts of ethylene glycol as a glycol component were charged into an ester exchange reactor, and 100 parts by mass of tetrabutyl titanate (catalyst) was added to this in an amount of 1 million parts by mass of the total dicarboxylic acid components. An esterification reaction was carried out at 160 to 240°C for 6 hours, and then the distillate was removed until the reaction product became transparent. Then, a polycondensation reaction was carried out under reduced pressure at 220 to 280°C to obtain polyester resin (A).

[0103] [Reference Example 21] Method for producing polyester film The polyester resin raw material was dried in a vacuum at 160°C for 4 hours, then fed to an extruder and melt-extruded at 285°C. After filtering through a filter with an average aperture of 5μm made by sintering and compressing stainless steel fibers, and then through a filter made by sintering stainless steel powder with an average aperture of 14μm, the sheet was extruded from a T-shaped die, and the sheet was wrapped around a mirror-finished casting drum with a surface temperature of 25°C at a casting speed of 30m / min using an electrostatic casting method, and cooled and solidified to obtain an unstretched film. After preheating this unstretched film to 80°C with a preheating roll, it was heated to 95°C from above and below using a radiation heater, and stretched 3.1 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls, and then cooled to 25°C with a cooling roll to obtain a uniaxially oriented (uniaxially stretched) film. Next, using a metering wire bar with a wire diameter of 0.1mm (#4), the following aqueous coating solution was measured so that the coating film thickness was 6μm, and this was applied to one side surface of the uniaxially stretched film.

[0104] <Coating fluid> An aqueous solution containing the following components and having a concentration of 5.0% calculated as polyester resin solids when the polyester resin solids are taken as 100 parts by mass. Polyester resin (A) obtained in Reference Example 20: 92.5% by mass Melamine-based crosslinking agent ("Nicalac" (registered trademark) MW12LF, manufactured by Sanwa Chemical Co., Ltd.): 5% by mass (solid content equivalent) Colloidal silica with a particle size of 140 nm: 2.5% by mass.

[0105] The uniaxially stretched film coated with the aqueous coating agent was held by clips at both widthwise ends and transported to an oven, where it was dried and preheated at an atmospheric temperature of 120°C. It was then continuously stretched 3.7 times in the widthwise direction in a 120°C stretching zone. The resulting biaxially oriented (biaxially stretched) film was then heat-treated for 10 seconds in a 230°C heating zone, after which it was cooled from 230°C to 120°C while undergoing a 5% relaxation treatment, and then cooled to 50°C. It was then slit parallel to the longitudinal direction to remove both widthwise ends, and then wound up to obtain a polyester film with a thickness of 50 μm.

[0106] [Table 1]

[0107] [Table 2]

[0108] [Example 1] A polyester film was obtained by using the polyester resin 1 obtained in Reference Example 1 according to the method of Reference Example 21. The properties of the obtained polyester film are shown in Table 3.

[0109] [Examples 2 to 15, Comparative Examples 1 to 4] Polyester films were obtained in the same manner as in Example 1, except that the polyester resin raw materials used were as shown in Tables 3 and 4. The properties of the obtained films are shown in Tables 3 and 4. In Examples 6, 7, and 8, the electrostatic castability deteriorated, so the cast speed was reduced to 20 m / min to produce the films, but the process stability and film b value were at an acceptable level.

[0110] [Table 3]

[0111] [Table 4] [Industrial Applicability]

[0112] According to the present invention, it is possible to provide a polyester film that is less colored while ensuring process stability. Since the polyester film according to the present invention has the above-mentioned excellent properties, it can be suitably used for optical films for displays, etc., which require high quality.

Claims

1. A polyester film comprising a base layer containing a polyester resin as a main component, the base layer having a linear oligomer content of 5 ppm or more and 100 ppm or less, and the base layer satisfying the following formula (I): 5 ppm≦Germanium element content (by mass)≦80 ppm (I)

2. The polyester film according to claim 1, wherein the base layer satisfies all of the following formulae (II) to (IV): 5 ppm≦Manganese element content (by mass)≦40 ppm (II) 4 ppm≦Sodium element content (by mass)≦40 ppm (III) 5ppm≦Metal element content (mass standard)≦100ppm (IV)

3. The polyester film according to claim 1 or 2, wherein the base layer satisfies the following formula (V): 15ppm≦phosphorus element content (mass standard)≦70ppm (V)

4. 4. The polyester film according to claim 3, wherein at least a portion of the phosphorus element is derived from phosphoric acid and sodium phosphate.

5. 3. The polyester film according to claim 1, wherein the base layer has a melt resistivity of 10.0 MΩ·cm or less.

6. The polyester film according to claim 1 or 2, further comprising a coating layer on at least one surface of the substrate layer.

7. 3. The polyester film according to claim 1, having an internal haze of 0.5% or less.

Citation Information

Patent Citations

  • Polyester film and its manufacture

    JP1998180844A

  • Method for producing polyester film

    JP2001089590A

  • Polyester resin composition and method for producing the same

    JP2019085504A

  • Method for producing polyester-based thermoplastic film, polyester-based thermoplastic film, and method for inspecting polyester-based thermoplastic film or resinous material therefor

    WO2018092414A1